Profile and Pattern of Hanging Cases at a Tertiary Care Hospital, Khammam; Telangana - Guntheti, Bharath Kumar; Khaja, Sheik; Singh, Uday Pal (Journal of Indian Academy of Forensic Medicine, 2016)
Out of 824 medico legal cases presenting to Dept. of Forensic Medicine, MGH, Khammam, TS  during one year (November 2014 to October 2015), 32 (n=32) hanging cases were reported and all of  them were taken into the present study. It was observed that the most vulnerable age group was 21 to 30  years [75.00%] in both sexes, with male to female ratio being 3:1. Males, Married, Hindu by religion, from  rural area accounted for 71.87 %. 24[75.00%] belonged to low income group. Preferred place of hanging  was indoor setting in 31[96.81%] cases. Financial problem was the main cause of committing suicidal  hanging. Marital unhappiness, chronic non-curable illness, domestic violence were the other main  causative factors of hanging. Hanging was complete in 24[75.00%] and was atypical in 22 [68.75%]  cases. Ligature material was present in 31 cases, it was above the level of thyroid cartilage in  28[87.50%], the ligature mark was oblique in 31[96.87%], deep in 26[81.25%].Rope was used as ligature  material by 24[75.00%]. Salivary discharge was observed in 14[43.75%] cases. Protrusion of tongue was  seen in 12[37.50%]. Asphyxial signs and congestion of organs, soft tissue petechial hemorrhage was  seen in 2 [6.25%], intimal tears of carotid artery in 4[12.50%]cases , fracture of hyoid bone in 7[2187%]  cases and no thyroid cartilage fracture were seen. The study objective was to find out the epidemiological  findings, pattern of hanging and identifying appropriate reasons
Keywords: Hanging; Incidence; Ligature material; place; Income; Education